Honoring the Ancestors: Toward an Afrocentric Theology of Liberation. (May 2013) - Clark, Adam
This article puts forth an argument for Afrocentric orientation in Black theology. First-generation Black theologians used the civil rights and Black power movements as primary sources for a theology of liberation. This article explores Afrocentricity as a moral resource for a new generation of Black pastors and theological scholars in carving out a theology of liberation from their own history and culture. The dialogue between Afrocentricity and Christian faith is not without pitfalls. Some Black churches argue that Afrocentricity is a hostile diversion from faith in Jesus Christ. Afrocentrists, in the main, claim that Christianity is irredeemably Eurocentric; it stunts the development of people of African descent. Building on the works of James Cone, Molefi Asante, and Maulana Karenga, I argue for a concept of double belonging; one can be nurtured by and belong to African and Christian traditions at the same time. I conclude with a brief discussion of the liberatory significance of Afrocentricity for the Black church.